The System of Standardization of Education in the Russian Federation Celebrates a Quarter of a Century - S. V. Korshunov (Высшее образование в России)
The article analyzes of results of the development of three  generations of federal state educational standards. The author dwells on their features and the principles of construction based on standardization of content of education and the requirements to learning results. Special attention is paid to the role of federal educational and methodical associations in the development ofeducational standards, approximate educational programs, normative documents and methodical materials in the sphere of higher education. The author also considers the role and value of theapproximate main educational program and reveals the discrepancy between the status of the approximate main educational program as obligatory when developing programs of higher education  institutions, and the regulations of the legislation in the field of education